BIOGAS PRODUCTION POTENTIAL IN ANAEROBIC DIGESTION OF SWINE MANURE WITH DIFFERENT SOLID FRACTION CONCENTRATIONS AND TEMPERATURES - Costa, Adriano Adelson; Silva, Maira Oliveira; Paron, Marcos Eduardo; Carvalho, Josirley de Fátima Corrêa; Júnior, Jorge de Lucas; Sagula, Alex Luiz; Fernandes, Aline; Cangani, Max Ternero; Azevedo, Sergio Santos; Soto, Francisco Rafael Martins (Revista de Estudos Ambientais, 2017)
This work aimed to evaluate the biogas production potential of swine manure (SM) under different temperatures through the use of experimental biodigesters (EB), investigating the physical, chemical and microbiological parameters of the process. The experiment consisted of three treatments a) with solid fraction separation (WSSF), b) without solid fraction separation (W-SSF) and c) solid fraction only (OSF). The assays were performed in triplicate and submitted to room temperature (RT) (13.36 to 23.71° C) and to controlled temperature (30.00ºC), during 28 days. The average biogas production in the EB was 390.41 ml (WSSF), 390.53 ml (W-SSF) and 400.53 ml (OSF), at RT and 393.00 ml (WSSF), 393.00 ml (W-SSF) and 390.67 ml (OSF) at 30.00ºC. The results showed that significant differences occurred in the biogas production due to the different treatments and temperatures. The highest average reduction of parameters as a function of treatment and temperature was 53.22% for total solids in WSSF (30°C), 10.73% for nitrogen in W-SSF (RT), 27.50% for phosphorus in the WSSF (TA), 63.55% for the COD in the W-SSF (TA), 99,10% for the total coliforms in the W-SSF (TA) and 99.59% for the thermotolerant coliforms in the WSSF (30°C).